Design a Mathematical Planning Approach to Optimize the Supply Chain Taking Into Account Uncertainties In Distributors - Chetthamrongchai Paitoon; Dayupay Johnry; Alshiqi Sevdie; Alghazali Tawfeeq Abdulameer Hashim; Iswanto A. Heri; Cavaliere Luigi Pio Leonardo; Al-Nussairi Ahmed Kateb Jumaah; Mohmmed Karrar Hatif; Kadhim Mustafa M. (Foundations of Computing and Decision Sciences, 2022)
With the globalization of markets and increasing competition in global markets, the attempts of organizations to survive in this market has increased and has resulted in the emergence of the philosophy of Supply Chain Management. There is uncertainty in the reliability of supply chain facilities for reasons such as natural disasters, terrorist attacks, labor errors, and weather conditions. Therefore, when making strategic decisions, the system will continue to operate with minimal damage. Over the course of this study, the uncertainty of supplier layers in the supply chain has been modeled. To meet that aim, the issue of supply chain, including producers, warehouses, suppliers and consumers are considered. To calculate the cost of breakdowns due to the non-functioning of distributors, the scenario-building method has been utilized. Finally, the desired model is solved with Gomez software and the results are presented. The result of the study demonstrate the efficiency of this model in the facility location decision-making in supply chains.